2019
DOI: 10.1002/jts.22359
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Olfactory Stimulation for Improvement of Sleep Quality in Patients With Posttraumatic Stress Disorder: A Randomized Exploratory Intervention Trial

Abstract: Posttraumatic stress disorder (PTSD) is characterized by sleep impairment and nightmares. As pleasant odors presented during sleep affect the emotional tone of dreams without inducing arousal, we investigated whether sleep patterns in PTSD can be improved via nocturnal olfactory stimulation. Participants were 40 inpatients with PTSD (n = 35 women; age range: 20–59 years) who completed a randomized, patient‐blind, placebo‐controlled trial. Baseline measurement for 5 consecutive nights was followed by a 5‐night … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…33 Further, the emerging sequelae, including sweating, anxiety, palpitation, edema of lower limbs, smell reduction, and taste change, were all psychological responses and associated with posttraumatic stress disorder (PTSD). [34][35][36] In our results, anxiety was universal in all subjects, no matter the severe or the non-severe. This indicated that the psychological comfort after hospital discharge of COVID-19 should not be neglected.…”
Section: Discussionsupporting
confidence: 51%
“…33 Further, the emerging sequelae, including sweating, anxiety, palpitation, edema of lower limbs, smell reduction, and taste change, were all psychological responses and associated with posttraumatic stress disorder (PTSD). [34][35][36] In our results, anxiety was universal in all subjects, no matter the severe or the non-severe. This indicated that the psychological comfort after hospital discharge of COVID-19 should not be neglected.…”
Section: Discussionsupporting
confidence: 51%
“…Early dream researchers used straightforward techniques of odour presentation, such as spraying odorants on the sleeping person’s pillow, to explore whether being exposed to odour can modify sleep mentation and its content [ 27 ]. Current scientific studies, in which simple odour administration techniques have been superseded by sophisticated olfactometry, have corroborated the notion that smells can indeed affect some aspects of sleep mentation [ 16 , 18 , 28 ]. Even so, it is rare for olfactory stimuli to be incorporated into MSEs [ 18 , 19 , 29 ], be it directly, so that individuals report dreams about the stimulus used for exposure, or indirectly, that is, by triggering the appearance of stimulus-related themes.…”
Section: Introductionmentioning
confidence: 99%
“…We included all studies reporting on sleep outcomes but, with few exceptions (Cook, Harb, et al, 2010;Jacobs-Rebhun et al, 2000;Raskind, Peskind, Chow, et al, 2018;Schäfer et al, 2019;Talbot et al, 2014), studies did not report a power calculation for sleep outcomes. In addition, a small proportion of studies addressing sleep reported a post hoc analysis indicating insufficient power to detect differences between treatment arms (Bormann et al, 2018;Cates et al, 2004;El-Solh et al, 2017;Galovski, Harik, et al, 2016;Harb, Cook, et al, 2019;Krakow et al, 2001;Krystal, Pietrzak, et al, 2016;Mack, 2014;Walters et al, 2019;Whitworth et al, 2019).…”
Section: Designmentioning
confidence: 99%
“…The majority of the included studies were conducted in outpatient settings. Only six studies took place in inpatient facilities (Ahmadi et al, 2015;Donner, Schellong, Hähner, Kerstin, et al, 2017;King et al, 2015;Peniston, 1986;Rosenbaum, Sherrington, and Tiedemann, 2015;Schäfer et al, 2019). Three studies combined inpatient and outpatient settings (Bartzokis et al, 2005;Keane et al, 1989;Peniston, 1986); two were administered remotely (Lange, Van de Ven, et al, 2001;; and one took place within the patient's household (Igreja et al, 2004).…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation